INDIVIDUAL, STRUCTURAL, ORGANIZATIONAL AND CULTURAL FACTORS ASSOCIATED WITH JOB SATISFACTION IN SCHOOL PRINCIPALS - Daniela Barrientos; Jazmin Galindo; Nayeli Yparraguirre; Trinidad Lettieri; Gonzalo Ferrari (Revista Científica Arbitrada de la Fundación MenteClara)
International evidence indicates a growing disillusionment with taking on school leadership positions and a significant decline in candidates for these roles, due to excessive demands, regulatory changes, and the increasing complexities of the role. Consequently, recruitment and retention strategies have focused on enhancing job satisfaction among school principals. Furthermore, it is worth noting that, despite their significant influence on school improvement and student learning, principals are studied less frequently than other school actors. Therefore, this article aims to investigate the factors that most significantly impact the job satisfaction of school leaders. The review results show that this phenomenon is complex and that multiple factors can lead to either job satisfaction or dissatisfaction among principals. It also highlights that different outcomes in job satisfaction can be explained by the local characteristics of the school and the cultural contexts principals encounter in their work. The findings suggest that it is necessary to continue investigating this knowledge gap to contribute to the development of public policies aimed at promoting principals' job satisfaction through support programs and professional development opportunities. This, in turn, would help attract and retain qualified, committed principals, ultimately leading to improvements in educational quality.